Variation of cow’s milk composition across different daily milking sessions and feasibility of using a composite sampling - Carlos Bondan; Jéssica Aneris Folchini; Mirela Noro; Karine Martini Machado; Eduardo Muhls; Félix Hilário Diaz González (Ciência Rural)
ABSTRACT: This study vised to detect possible changes in chemical and cellular composition of cow’s milk at different milking sessions and to test if proportional or composite milk sampling can be used instead of separate milk analysis. Two experiments were conducted: one in cows milked thrice daily and the other one in cows milked twice daily. In both experiments, three milk samples were collected from each cow in each milking session in order to determine milk composition at each milking; to have a composite sample, i.e., a single sample from the same aliquots of milk from each milking session; and to have a proportional sample, i.e., a single sample from each milking session in a volume proportional to milk volume yielded. Fat content and fat to protein ratio were higher in the afternoon on both experiments. Protein content was larger in the afternoon on cows milked twice daily, but not on cows milked thrice daily. Lactose level was not different across the milking sessions in any of the experiments. The urea level was higher in the afternoon and evening milking on cows milked thrice daily, and in the morning milking on cows milked twice daily. Somatic cell count did not differ between milking in any experiment. No difference in milk composition was noted between proportional and composite samples on cows milked thrice or twice daily. The collection of proportional and composite samples is recommended in twice or thrice daily milking sessions so that the analysis of milk components becomes more easy and cheap.